Македонија и нејзините соседи - Стефанија, Драги; Миодонска, Лилијана (Slavia Centralis, 2020)
Macedonia and its neighborsMany aspirations to conquer Macedonia and to annihilate it have continued into the present. The Greeks have claimed a legal right to the name Macedonia, the Macedonian language and history ever since Alexander the Great. The Serbs do not acknowledge the Macedonian Orthodox Church, as if Macedonia were a pagan country. The Bulgarians claim that the Macedonian language is a Bulgarian dialect, and the Albanians demand one third of Macedonia (the Western part), which is inhabited by an Albanian minority.
Keywords: Macedonia; the Macedonian language; inter-state relations; intercultural dialogue